2017
DOI: 10.1177/2158244017697168
|View full text |Cite
|
Sign up to set email alerts
|

What Is Eve Teasing? A Mixed Methods Study of Sexual Harassment of Young Women in the Rural Indian Context

Abstract: Eve teasing was identified as a significant community problem through a community-based participatory process with nine villages in Punjab, India. Eve teasing is a common euphemism in South Asia for sexual harassment of women in public areas by men. The purpose of this study was to characterize the meaning of eve teasing in the rural context, especially among female youth, and to develop a means to measure its occurrence. Mixed methods were utilized including focus group discussions (FGDs), semistructured inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Eve-teasing is a common form of emotional and sexual violence against girls, and includes “staring, stalking, passing comments, and inappropriate physical touch” by boys and men [42]. Consequences for girls may include restrictions on mobility, inability to go to school or work, blame and disrespect from family members [42]. Parents were the most common perpetrators of violence against girls in our study and around a quarter reported witnessing violence between their parents.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Eve-teasing is a common form of emotional and sexual violence against girls, and includes “staring, stalking, passing comments, and inappropriate physical touch” by boys and men [42]. Consequences for girls may include restrictions on mobility, inability to go to school or work, blame and disrespect from family members [42]. Parents were the most common perpetrators of violence against girls in our study and around a quarter reported witnessing violence between their parents.…”
Section: Discussionmentioning
confidence: 90%
“…Emotional violence was highly prevalent in our study and included being insulted, humiliated and intimidated. Eve-teasing is a common form of emotional and sexual violence against girls, and includes “staring, stalking, passing comments, and inappropriate physical touch” by boys and men [42]. Consequences for girls may include restrictions on mobility, inability to go to school or work, blame and disrespect from family members [42].…”
Section: Discussionmentioning
confidence: 99%
“…Stranger harassment in public spaces also reduces women's perceptions of safety while travelling alone at night (Macmillian et al, 2000) and such experiences indirectly contribute to restricted movements (Fairchild and Rudman, 2008). Adolescent and young adult experiences of 'Eva teasing' (a form of street harassment) are associated with negative emotions and restricted movements (Talboys et al, 2017), avoidance of school (Bhagavatheeswaran et al, 2016), and poorer mental health outcomes and suicidal ideation (Talboys, 2015). Further, adolescent females are twice as likely as adolescent males to report Running head: STREET HARASSMENT TYPOLOGY 6 worrying about stranger danger when considering neighbourhood safety (Craver et al, 2008), more frequently report a sense of unease when they are stared at by a stranger or are alone at night in the street (Zani et al, 2001), and are more likely to experience street harassment (Meza-de-Luna and García-Falconi, 2015).…”
mentioning
confidence: 99%
“…Gender norms also manifest through harassment and violence, daily realities for many young women in India. Eve teasing (street harassment) and sexual harassment have far-reaching consequences, including both short and long-term socio-emotional consequences and limited access to education for victims (Talboys et al, 2017). Participants' stories highlighted harassment experienced on public transportation, which other studies have found to be commonplace (Dhillon & Bakaya, 2014;Gekoski, Gray, Adler, & Horvath, 2017;Leach & Sitaram, 2007;Tripathi, Borrion, & Belur, 2017).…”
Section: Discussionmentioning
confidence: 99%